A Concise Dictionary of English Idioms - Phythian, B. A. (London Hodder & Stoughton, 1993)
This revised edition provides a simple, but wide-ranging guide to the usage and meaning of the most commonly used idiomatic expressions in current English, with almost 900 new entries in a new format. By the author of "A Concise Dictionary of Correct English" and "English Slang".
Keywords: English language--Idioms -- English language--Errors of usage -- English language--Usage